Risk factors for specific causes of death following pediatric heart transplant: An analysis of the registry of the International Society of Heart and Lung Transplantation. (18th September 2015) - Vanderlaan, R. D.; Manlhiot, C.; Edwards, L. B.; Conway, J.; McCrindle, B. W.; Dipchand, A. I.
Abstract: We sought to determine temporal changes in COD and identify COD‐specific risk factors in pediatric primary HTx recipients. Using the ISHLT registry, time‐dependent hazard of death after pediatric HTx, stratified by COD, was analyzed by multiphasic parametric hazard modeling with multivariable regression models for risk factor analysis. The proportion of pediatric HTx deaths from each of cardiovascular cause, allograft vasculopathy, and malignancy increased over time, while all other COD decreased post‐HTx. Pre‐HTx ECMO was associated with increased risk of death from graft failure (HR 2.43; p < 0.001), infection (HR 2.85; p < 0.001), and MOF (HR 2.22; p = 0.001), while post‐HTx ECMO was associated with death from cerebrovascular events/bleed (HR 2.55; p = 0.001). CHD was associated with deaths due to pulmonary causes (HR 1.78; p = 0.007) or infection (HR 1.72; p < 0.001). Non‐adherence was a significant risk factor for all cardiac COD, notably graft failure (HR 1.66; p = 0.001) and rejection (HR 1.89; p < 0.001). Risk factors related to specific COD are varied across different temporal phases post‐HTx. Increased understanding of these factors will assist in risk stratification, guide anticipatory clinical decisions, and potentially improve patient survival.